PRINTING QUALITY CONTROL OF AICE PRODUCT PACKAGING AT PT TEMPRINA MEDIA GRAFIKA PACKAGING BEKASI - Riky Rusdianto; Anton Hadiwibowo; Mukhyidin Djaiz (Kreator, 2020)
The process of controlling the quality of the packaging mold in this final project aims to determine the factors that must be considered, carry out the control process and perform problem solving using a fishbone chart cause and effect diagram. To achieve good print quality, it is necessary to know the problem factors that can affect print quality. This final project focuses on the process of controlling the packaging mold for Aice products. This control process is carried out from the process of icoming the raw materials to the out going of the finished product. This writing uses a descriptive method, which is a writing method that describes and describes the quality control of Aice's product packaging prints. Methods were collected from literature study and observation at PT. Temprina Media Grafika Packaging Bekasi about 3 months. Measurements in quality control use a check list form, color range and cause and effect diagrams fishbone chart. The results of this final project show that in the process of controlling the quality of a good packaging mold, it is necessary to pay attention to factors that can affect quality such as human, material, method, machine and environment. The control process is carried out in several stages, namely control of raw materials, control of the production process, sampling of packaged printed products, controlling the finished product, then solving problems using a fishbone chart cause and effect diagram. To maintain the quality of the products produced, it is necessary to add supporting components in the process of controlling the quality of the mold, increasing optimization of machine maintenance and increasing the skills of human resources. Keywords— Control, print quality, descriptive, fishbone chart